Development of composting process by different lignocellulolytic fungi using oil palm industrial waste in rotary drum bioreactor - Alam, Md. Zahangir; Kabbashi, Nassereldeen Ahmed; Othman, Ahmadi Amri (2006)
Composting is one of the biological processes that has been considered to be the most suitable ways of converting organic wastes into products that are beneficial for plant growth. Solid state bioconversion (SSB) of mixed substrate such as EFB and POME by different lignocellulolytic microorganisms using rotary drum bioreactor was carried out in lab-scale. The microorganisms were: Phanerocheate chrysosporium, Trichoderma, Aspergillus and Penicillium. The composting process was involved through SSB by four different types of fungi based on their activities in the rotary drum bioreactor for two months. The mature compost was evaluated with the different parameters especially, C/N ratio, germination index, pH and color. The results showed that the C/N ratio was decreased from 70 to 25 after 20 days of composting process. The germination index of 50-70 indicated that the compost produced was a phyto toxic-free product and merely achieved mature compost within 45 days of composting time.